BEN3/BIG2 ARF GEF is Involved in Brefeldin A-Sensitive Trafficking at the trans-Golgi Network/Early Endosome in Arabidopsis thaliana - Kitakura, Saeko; Adamowski, Maciek; Matsuura, Yuki; Santuari, Luca; Kouno, Hirotaka; Arima, Kohei; Hardtke, Christian S; Friml, Jirí; Kakimoto, Tatsuo; Tanaka, Hirokazu (Plant and Cell Physiology, 2017)
Membrane traffic at the trans-Golgi network (TGN) is crucial for correctly distributing various membrane proteins to their destination. Polarly localized auxin efflux proteins, including PIN-FORMED1 (PIN1), are dynamically transported between the endosomes and the plasma membrane (PM) in the plant cells. The intracellular trafficking of PIN1 protein is sensitive to the fungal toxin brefeldin A (BFA), which is known to inhibit guanine nucleotide exchange factors for ADP ribosylation factors (ARF GEFs) such as GNOM. However, the molecular details of the BFA-sensitive trafficking pathway have not been fully revealed. In a previous study, we identified an Arabidopsis mutant BFA-visualized endocytic trafficking defective 3 (ben3) which exhibited reduced sensitivity to BFA in terms of BFA-induced intracellular PIN1 agglomeration. Here, we show that BEN3 encodes a member of BIG family ARF GEFs, BIG2. BEN3/BIG2 tagged with fluorescent proteins co-localized with markers for the TGN/early endosome (EE). Inspection of conditionally induced de novo synthesized PIN1 confirmed that its secretion to the PM is BFA sensitive, and established BEN3/BIG2 as a crucial component of this BFA action at the level of the TGN/EE. Furthermore, ben3 mutation alleviated BFA-induced agglomeration of another TGN-localized ARF GEF, BEN1/MIN7. Taken together, our results suggest that BEN3/BIG2 is an ARF GEF component, which confers BFA sensitivity to the TGN/EE in Arabidopsis.
Keywords: Green Fluorescent Proteins; Cell Compartmentation; Phenotype; ADP-ribosylační faktory; Arabidopsis Proteins; Cell Membrane; Codon, Nonsense; výměnné faktory guaninnukleotidů; Protein Transport; Guanine Nucleotide Exchange Factors; trans-Golgi Network; kompartmentace buňky; ADP-Ribosylation Factors; proteiny huseníčku; nesmyslný kodon; zelené fluorescenční proteiny; transport proteinů; Endosomes; Cloning, Molecular; alely; Alleles; Arabidopsis; klonování DNA; Brefeldin A; fenotyp; trans-Golgiho síť; semenáček; buněčná membrána; Seedlings; endozomy; brefeldin A